Differences in milling speed and sintering speed using cad/cam technique on the marginal gap of zirconia dental crown - Murti Indrastuti; Sri B. Barunawati; Nadya K. Putri (Indonesian Journal of Prosthodontic, 2025)
Computer-Aided Design and Computer-Aided Manufacturing (CAD/CAM) is a digital approach to fabricating dental restorations, including zirconia crowns. Compared to conventional techniques, CAD/CAM offers a more efficient and precise workflow. The laboratory workflow in CAD/CAM process provides advantages such as high accuracy and a broader selection of materials, although it generally requires more time than chairside workflows. Manufacturing parameters—particularly milling speed and sintering speed—may influence the mechanical characteristics of restorations, especially marginal gaps, which are critical for long-term clinical success. Excessive marginal gaps can lead to restoration failure. This study aims to examine the effects of milling and sintering speeds on the marginal gap of zirconia crowns made using CAD/CAM technology. This experimental laboratory study involved 24 zirconia crowns divided into six groups based on combinations of three milling speeds (fast, normal, gentle) and two sintering speeds (conventional and speed). Marginal gaps were measured using micro-computed tomography (micro-CT), and data were analyzed with a two-way ANOVA followed by a Post-Hoc LSD test. Results revealed significant differences in marginal gaps related to both milling and sintering speeds (p < 0,05). The combination of gentle milling and speed sintering resulted in the smallest marginal gap (86,36 μm), while fast milling with conventional sintering produced the largest (118 μm). All values remained within the clinically acceptable range (50–120 μm). In conclusion, both milling speed and sintering speed significantly affect the marginal gap of zirconia dental crowns, highlighting the importance of optimizing these parameters for improved restoration quality.